2022
DOI: 10.3390/ijms23052899
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Gentamicin-Loaded Arabinoxylan-Sodium Alginate Films as Antibacterial Wound Dressing

Abstract: Biopolymer-based antibacterial films are attractive materials for wound dressing application because they possess chemical, mechanical, exudate absorption, drug delivery, antibacterial, and biocompatible properties required to support wound healing. Herein, we fabricated and characterized films composed of arabinoxylan (AX) and sodium alginate (SA) loaded with gentamicin sulfate (GS) for application as a wound dressing. The FTIR, XRD, and thermal analyses show that AX, SA, and GS interacted through hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…The water vapor transmission rate (WVTR) denotes one of the basic physical property of wound dressings as it helps regulate the moist environment, assess the moisture transfer and exudate absorption rate along with controlling water loss during the wound healing process [ 166 , 167 ]. Moreover, as discussed above, ideal wound dressings should also allow moisture transport (for efficient gas exchange) apart from good wound exudates absorption ability for the wound healing process.…”
Section: In Vitro Characterization Methods For Wound Dressing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water vapor transmission rate (WVTR) denotes one of the basic physical property of wound dressings as it helps regulate the moist environment, assess the moisture transfer and exudate absorption rate along with controlling water loss during the wound healing process [ 166 , 167 ]. Moreover, as discussed above, ideal wound dressings should also allow moisture transport (for efficient gas exchange) apart from good wound exudates absorption ability for the wound healing process.…”
Section: In Vitro Characterization Methods For Wound Dressing Materialsmentioning
confidence: 99%
“…Several methods are currently being employed for determining the antimicrobial properties of dressings such as the determination of zone of inhibition (ZOI) using disc-and well-diffusion methods while agar, and broth dilution methods are used to determine minimum inhibitory concentration (MIC) [ 174 , 190 , 191 , 192 ]. Mostly, the disc diffusion method is used to estimate the antimicrobial properties of the dressing materials or antibacterial agent loaded dressing [ 160 , 161 , 167 , 170 , 177 , 192 , 193 , 194 ]. Briefly, in this method, the dressing materials (hydrogel, films, sponge, etc.)…”
Section: In Vitro Characterization Methods For Wound Dressing Materialsmentioning
confidence: 99%
“…The study of the mechanical properties showed that tensile strengths (TS) of the films ranged between 2.31 and 2.75 MPa, while the percent elongations at break (% EAB) varied from 54% to 67%. Additionally, the TS of the films increased, and EAB decreased with increasing arabinoxylan concentration in the films [169]. Moreover, the tensile strengths of the GS-loaded films were slightly higher than that of blank films.…”
Section: Alginate Wound Dressings With Antibiotic and Antiseptic-load...mentioning
confidence: 90%
“…Alzarea et al [169] proposed wound dressing composed by arabinoxylan (AX) and sodium alginate (SA) loaded with gentamicin sulfate (GS). Films for the investigation were prepared by the solvent casting technique, and different amounts of AX and SA were used with glycerol added as the plasticizer.…”
Section: Alginate Wound Dressings With Antibiotic and Antiseptic-load...mentioning
confidence: 99%
“…Today, the commercialisation of electrospinning equipment is advancing quickly. The most popular electrospinning methods include bubble electrospinning, melt electrospinning, coaxial electrospinning, self-bundling electrospinning, and nano-spider electrospinning [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Fibre electrospinning processes can be used to create polymer nanofibres (50–1000 nm) (wet or hot melt electro-spinning).…”
Section: Localised Delivery Systems For Wound Healingmentioning
confidence: 99%